DAMPAK DISRUPSI PENDIDIKAN KARENA PANDEMI COVID-19 DI SMA MUHAMMADIYAH 2 PEMALANG - Afifah Mufidah Muninggar; Febriyanto Arif Nugroho; Dani Anwar Hadi; Luthfatul Umayah (Buletin Literasi Budaya Sekolah, 2021)
The research aims to identify teaching and learning conditions in the pandemic era, prevention of media used by teachers before and before the pandemic, learning methods used by teachers, and the impact and constraints of students and teachers during learning in the pandemic era. This study uses a qualitative method. This research technique uses interviews, observations, direct observations of teachers when carrying out learning and strengthening character education, both in intracurricular activities and co-curricular and extracurricular activities. Based on the results of this study, educational disruptions in the pandemic era had an impact on learning activities at SMA Muhammadiyah 2 Pemalang. It is clear that the process of teaching and learning activities which include implementation activities, learning methods, learning media are not running as normal before the COVID-19 pandemic. It turns out that remote learning or in this network after implementing several problems that arise both from teachers as educators and from students as students.